" Russian-Turkish Relations and Current International Alliances in the Middle East A Study on Influence and Impact" - Muthanna F. Merie; Wadi, Abd al-Alim Fadil (Tikrit Journal For Political Science, 2017)
International relations are affected by the interests that may be achieved by States or if those interests are harmed as a result of internal and external factors that are exposed to this or that state. The bilateral international relations are also affected by the alliances to which one or both sides of the relationship is involved. A set of geopolitical, economic, security and ideological interests negatively and positively. Such relations were also affected by the policy of axes and international alliances, which have long been joined by the two countries to contradictory alliances that have strained their relations. Turkey is a member of the four-party alliance and Turkey is a member of the Islamic alliance and then of the international coalition to fight the oppressive organization and the terrorist groups in Iraq and Syria. Each of these alliances has its objectives and members whose views differ from those of other member states, Hence, the impact on relations between Russia and Turkey was clear.